2008
DOI: 10.1016/j.jamcollsurg.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Participation of Older Women in Surgical Trials

Abstract: BACKGROUND-Older participants are often excluded from clinical trials, precluding a representative sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Last, a lack of financial compensation for time was endorsed as a participation barrier, particularly among non-White participants. Our findings are supported by research in older clinical populations (e.g., patients with diabetes or undergoing surgery) that report similar barriers, including insufficient time [15, 16], inadequate transportation [15], and an unwillingness to travel to the study location [28]. Findings from the current study extend prior work by suggesting that these barriers are an issue for increasing involvement in Center-approved studies among a cohort who has already joined the registry and committed to its annual visit.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Last, a lack of financial compensation for time was endorsed as a participation barrier, particularly among non-White participants. Our findings are supported by research in older clinical populations (e.g., patients with diabetes or undergoing surgery) that report similar barriers, including insufficient time [15, 16], inadequate transportation [15], and an unwillingness to travel to the study location [28]. Findings from the current study extend prior work by suggesting that these barriers are an issue for increasing involvement in Center-approved studies among a cohort who has already joined the registry and committed to its annual visit.…”
Section: Discussionsupporting
confidence: 81%
“…Focus group findings from AD caregivers suggest that a lack of direct medical benefit, testing procedures, insufficient time, research skepticism, and difficulty coping with the AD diagnosis are major participation obstacles [13]. Survey and interview data suggest similar barriers are expressed in broader clinical research areas, such as cancer and diabetes trials, including caregiver unwillingness [14, 15], discomfort with research methods [10, 16], insufficient time [15, 16], inadequate transportation [15], and patients’ deteriorating health [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…The time commitment required to participate in a clinical trial is identified as an important barrier to participation. The time costs included the inconvenience of trial related requirements and visits; travel; following specific regimens and completing a daily diary log [6] , [9] , [42] , [43] . The time to arrange transport was the greatest barrier for participation [14] , [26] and this is likely to be due to the lack of clinical trials available in rural areas [27] .…”
Section: Resultsmentioning
confidence: 99%
“…In the clinical trial setting altruism is seen as an act for the betterment of mankind [43] . The most common explanations of altruism within this review was the act of unselfishness for contribution to medicine and science [7] , [8] , [10] , [19] , [25] , [30] , and to help others, be it the community or nursing care, family or future patients [8] , [9] , [16] , [19] , [23] , [38] , [42] , [44] . This review identified that the act of altruism is most likely to be observed within the haematology and oncology settings with it occurring less prominently in settings such as cardiology, gastrointestinal diseases and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…l Some of these articles described lists of issues, 83 which were useful, but some authors went beyond this to develop understanding. Russell et al 87 used content analysis but embedded it in known literature to move beyond a simple list.…”
Section: Systematic Mapping Review Of Published Qualitative Research mentioning
confidence: 99%